Reduced Endoplasmic Reticulum Stress-Mediated Autophagy Is Required for Leptin Alleviating Inflammation in Adipose Tissue - Gan, Lu; Liu, Zhenjiang; Luo, Dan; Ren, Qian; Wu, Hua; Li, Changxing; Sun, Chao (Frontiers in Immunology, 2017)
Leptin is an adipocyte-derived hormone and maintains adipose function under challenged conditions. Autophagy is also essential to maintain cellular homeostasis and regulate characteristics of adipose tissue. However, the effects of leptin on autophagy of adipocyte remain elusive. Here, we demonstrated endoplasmic reticulum (ER) stress and leptin were correlated with autophagy and inflammation by transcriptome sequencing of adipose tissue. Leptin-mediated inhibition of autophagy was involved in upstream reduction of ER stress proteins such as Chop, GRP78 and Atf4, since blockage of autophagy using pharmacological approach had no effect on tunicamycin-induced ER stress. Moreover, we determined KLF4, the potential transcriptional factor of Atf4, was required for the leptin-mediated autophagy in the regulation of adipocyte inflammation. Importantly, ATF4 physically interacted with ATG5 and subsequently formed a complex to promote adipocyte autophagy. Further analysis revealed that Atg5, a core component of autophagosome, was the target for leptin-mediate autophagy. In addition, leptin alleviated ER stress-induced inflammation by reducing autophagy-mediated degradation of IκB in adipocytes. Exogenous leptin treatment also ameliorated autophagy and inflammation of white adipose tissue in ob/ob mice. Taken together, our results indicated that leptin inhibited ER stress-mediated autophagy and inflammation through the negatively regulation of Atf4/Atg5 complex in adipocytes. These findings identify a new potential means for intervention of autophagy to prevent or treat obese caused metabolic syndrome of mammals.